Method for preparing double-layer coated negative pole piece
By regulating the mixing ratio of active materials and auxiliary materials of the double-layer coated negative electrode sheet of lithium-ion battery, it ensures that the compaction density difference between the upper and lower coatings reaches the ideal goal, and solves the problem of difficult to efficiently control the compaction density difference in the prior art, and achieves the improvement of battery performance and development efficiency.
Patent Information
- Application Number
- CN202411926201.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-25
- Publication Date
- 2025-04-29
AI Technical Summary
The prior art is difficult to efficiently control the compaction density difference of the upper and lower coatings of the double-layer coated negative electrode sheet of lithium-ion battery, resulting in the failure of rate performance and cycling performance to achieve the ideal target.
Before preparing the active layer slurry, the types and mixing ratios of the first and second negative electrode active materials and auxiliary materials are adjusted so that the 1T powder compaction density reaches a predetermined value, ensuring that the compaction density difference between the first and second active layers reaches the ideal goal.
It realizes efficient control of the compaction density difference between the upper and lower coatings of the negative electrode sheet, improves the cycle life and charging rate of lithium-ion batteries, improves the battery development efficiency, and saves time and economic costs.
Smart Images

Figure CN119905524A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of lithium ion batteries, and in particular to a method for preparing a double-layer coated negative electrode sheet. Background Art
[0002] Lithium-ion batteries are widely used in the fields of consumer batteries, power batteries and energy storage batteries due to their high operating voltage, high energy density and environmental friendliness. They also have broad application prospects in the fields of aerospace, national defense and military industries. As people's quality of life improves, the requirements for fast charging performance of various electronic devices are getting higher and higher. Related technologies report that by preparing a double-layer coated negative electrode sheet and making the upper and lower coatings have a compaction density difference, the rate performance and cycle performance of lithium-ion batteries can be improved. However, it is currently impossible to efficiently control the compaction density difference between the upper and lower coatings to reach the ideal target value, so that a double-layer coated negative electrode sheet with a compaction density difference cannot be efficiently prepared. Therefore, it is urgent to develop a method for preparing a double-layer coated negative electrode sheet that can efficiently control the compaction density difference between the upper and lower coatings to achieve the ideal goal. Summary of the invention
[0003] The present invention aims to solve one of the technical problems in the related art to at least some extent. To this end, one object of the present invention is to provide a method for preparing a double-layer coated negative electrode sheet, which can efficiently control the compaction density difference between the upper and lower coatings to achieve an ideal target.
[0004] Specifically, the present invention provides a method for preparing a double-layer coated negative electrode sheet, comprising the following steps:
[0005] The first negative electrode active material and the first auxiliary material are mixed and dried to obtain a first mixture, and the 1T powder compaction density of the first mixture reaches a first predetermined value by adjusting the raw material types and / or the mixing ratio, and the mixing ratio at this time is recorded as the first ratio and the raw material types at this time are recorded;
[0006] The second negative electrode active material and the second auxiliary material are mixed and dried to obtain a second mixture, and the 1T powder compaction density of the second mixture reaches a second predetermined value by adjusting the raw material types and / or the mixing ratio, and the mixing ratio at this time is recorded as the second ratio and the raw material types at this time are recorded, wherein the first predetermined value is greater than the second predetermined value;
[0007] Mixing the determined first negative electrode active material, the first auxiliary material and the first solvent in a determined first ratio to obtain a first active layer slurry;
[0008] Mixing the determined second negative electrode active material, the second auxiliary material and the second solvent in a determined second ratio to obtain a second active layer slurry;
[0009] Applying the first active layer slurry on the surface of the negative electrode current collector to form a first active layer;
[0010] The second active layer slurry is coated on the surface of the first active layer to form a second active layer, thereby obtaining a double-layer coated negative electrode sheet.
[0011] Before preparing the active layer slurry, the present invention first regulates the type and / or mixing ratio of the first negative electrode active material and the first auxiliary material, and the type and / or mixing ratio of the second negative electrode active material and the second auxiliary material, so that the 1T powder compaction density of the first mixture and the second mixture is within a predetermined range, and then the active layer slurry is prepared, coated, and rolled after the type and mixing ratio of the raw materials are determined, so that the compaction density difference between the formed first active layer and the second active layer can be ensured to reach the ideal target. Applying the negative electrode sheet of the present invention to the battery can improve the cycle life and charging rate of the battery.
[0012] The method of the present invention can control the compaction density difference between the first active layer and the second active layer to achieve the ideal target only from the raw material end, thereby improving the development efficiency of the battery and saving time and economic costs. The related art is to control the compaction density difference of the upper and lower coatings by controlling the compaction density of the graphite powder in the upper and lower coatings, but this method cannot ensure that the compaction density difference of the upper and lower coatings reaches the target difference. It is also necessary to first make a double-layer coated pole piece and measure the compaction density of the upper and lower coatings. If the compaction density difference does not reach the target difference, the compaction density of the graphite powder in the upper and lower coatings is further adjusted, and the process is repeated until the compaction density reaches the target difference, which leads to low development efficiency, cumbersome process, and high cost. The present invention avoids these problems in the related art.
[0013] According to some embodiments of the present invention, the first predetermined value is 1.7-2.2 g / cm 3 , preferably 1.7 to 2.0 g / cm 3 The second predetermined value is 1.3 to 1.8 g / cm 3 , preferably 1.5 to 1.8 g / cm 3 .
[0014] According to some embodiments of the present invention, the first auxiliary material includes one or more of a first binder, a first conductive agent, and a first dispersant. Optionally, the second auxiliary material includes one or more of a second binder, a second conductive agent, and a second dispersant.
[0015] According to some embodiments of the present invention, the mass ratio of the first negative electrode active material, the first conductive agent, the first dispersant, and the first binder is (94-97.4): (0.8-1.4): (0.2-1.5): (1.4-3.6).
[0016] According to some embodiments of the present invention, the mass ratio of the second negative electrode active material, the second conductive agent, the second dispersant, and the second binder is (96.4-99): (0-0.5): (0.5-1.5): (0.1-2.6).
[0017] According to some embodiments of the present invention, the proportion of the first conductive agent in the total mass of the first negative electrode active material and the first auxiliary material is greater than the proportion of the second conductive agent in the total mass of the second negative electrode active material and the second auxiliary material.
[0018] According to some embodiments of the present invention, the first binder and the second binder each include one or more of styrene-butadiene rubber, polyacrylic acid, sodium polyacrylate, polyacrylamide, polyvinyl alcohol, sodium alginate, polymethacrylic acid and carboxymethyl chitosan. Optionally, the first conductive agent and the second conductive agent each include one or more of superconducting carbon, acetylene black, carbon black, Ketjen black, carbon dots, carbon nanotubes, graphene and carbon nanofibers. Optionally, the first dispersant and the second dispersant each include one or more of sodium carboxymethyl cellulose 350, sodium carboxymethyl cellulose 500, sodium carboxymethyl cellulose 2300 and sodium carboxymethyl cellulose 2500.
[0019] According to some embodiments of the present invention, in the first active layer, the first binder includes polyacrylic acid, and the first dispersant includes sodium carboxymethyl cellulose; wherein the proportion of polyacrylic acid in the total mass of the first negative electrode active material and the first auxiliary material is less than the proportion of sodium carboxymethyl cellulose in the total mass of the first negative electrode active material and the first auxiliary material. Optionally, in the second active layer, the second binder includes polyacrylic acid, and the second dispersant includes sodium carboxymethyl cellulose; wherein the proportion of polyacrylic acid in the total mass of the second negative electrode active material and the second auxiliary material is greater than the proportion of sodium carboxymethyl cellulose in the total mass of the second negative electrode active material and the second auxiliary material.
[0020] According to some embodiments of the present invention, the first negative electrode active material and the second negative electrode active material each include graphite. Optionally, the graphite includes one or more of natural graphite, modified natural graphite, and artificial graphite.
[0021] According to some embodiments of the present invention, the compaction density of the first active layer is greater than the compaction density of the second active layer, and the porosity of the first active layer is less than the porosity of the second active layer. Optionally, the surface density ratio of the second active layer to the first active layer is 1:(0.1-9).
[0022] Additional aspects and advantages of the present invention will be given in part in the following description and in part will be obvious from the following description, or will be learned through practice of the present invention. BRIEF DESCRIPTION OF THE DRAWINGS
[0023] The above and / or additional aspects and advantages of the present invention will become apparent and easily understood from the description of the embodiments in conjunction with the following drawings, in which:
[0024] Figure 1 It is a schematic diagram of the structure of a double-layer coated negative electrode sheet prepared in an embodiment of the present invention.
[0025] Figure 2 It is a comparison chart of the equivalent 4.2C cycle performance of the batteries corresponding to Examples 1-3 and Comparative Examples 1-3.
[0026] Reference numerals:
[0027] 100, negative electrode current collector; 200, first active layer; 300, second active layer. DETAILED DESCRIPTION
[0028] Embodiments of the present invention are described in detail below, examples of which are shown in the accompanying drawings, wherein the same or similar reference numerals throughout represent the same or similar elements or elements having the same or similar functions. The embodiments described below with reference to the accompanying drawings are exemplary and are intended to be used to explain the present invention, and should not be construed as limiting the present invention.
[0029] In the description of the present invention, it should be understood that the terms "first" and "second" are used for descriptive purposes only and should not be understood as indicating or implying relative importance or implicitly indicating the number of technical features indicated. Thus, a feature defined as "first" or "second" may explicitly or implicitly include at least one of the features. In the description of the present invention, "multiple" means at least two, such as two, three, etc., unless otherwise clearly and specifically defined.
[0030] In the description of the embodiments of the present application, the term "and / or" is merely a term used to describe the association relationship of associated objects, indicating that three relationships may exist. For example, A and / or B may represent three situations: A exists, A and B exist at the same time, and B exists.
[0031] Related technologies report a method for preparing a double-layer coated negative electrode sheet, which improves the rate performance and cycle performance of lithium-ion batteries by controlling the powder compaction density of graphite in the upper and lower coatings so that there is a compaction density difference between the upper and lower coatings. However, this method cannot ensure that the compaction density difference between the upper and lower coatings reaches the ideal target difference. It is also necessary to first make a double-layer coated electrode sheet and measure the compaction density of the upper and lower coatings. If the compaction density difference does not reach the target difference, it is necessary to further adjust the powder compaction density of graphite in the upper and lower coatings and repeat until the compaction density reaches the target difference. Due to problems such as the double-layer coating process and coating characterization technology, screening graphite materials with suitable powder compaction density by making electrodes will inevitably reduce development efficiency. Therefore, it is necessary to develop a method for preparing a double-layer coated negative electrode sheet that can efficiently control the compaction density difference between the upper and lower coatings to achieve the ideal goal.
[0032] After research, it was found that the existence of a phase formed by auxiliary materials in the electrode coating will affect the compressive resistance of the coating, and then affect the compaction density of the coating. Based on this discovery, the present invention designs a method for preparing a double-layer coated negative electrode sheet. Before preparing the first and second active layer slurries, the method first regulates the type and / or mixing ratio of the first negative electrode active material and the first auxiliary material and the type and / or mixing ratio of the second negative electrode active material and the second auxiliary material, determines the mixing ratio and raw material type that can make the 1T powder compaction density of the first mixture and the second mixture within a predetermined range, and then prepares the active layer slurry, coating, and rolling after determining the type and mixing ratio of the raw materials, so as to ensure that the compaction density difference between the first active layer and the second active layer formed reaches the ideal target, that is, to ensure that the compaction density of the first active layer is greater than the compaction density of the second active layer. Applying the negative electrode sheet of the present invention to the battery can improve the cycle life and charging rate of the battery. The method of the present invention can control the compaction density difference between the first active layer and the second active layer to achieve the ideal target only from the raw material end, avoids the problems in the related art, improves the development efficiency of the battery, and saves time and economic costs.
[0033] Specifically, the present invention provides a method for preparing a double-layer coated negative electrode sheet, comprising the following steps:
[0034] The first negative electrode active material and the first auxiliary material are mixed and dried to obtain a first mixture, and the 1T powder compaction density of the first mixture reaches a first predetermined value by adjusting the raw material types and / or the mixing ratio, and the mixing ratio at this time is recorded as the first ratio and the raw material types at this time are recorded;
[0035] The second negative electrode active material and the second auxiliary material are mixed and dried to obtain a second mixture, and the 1T powder compaction density of the second mixture reaches a second predetermined value by adjusting the raw material types and / or the mixing ratio, and the mixing ratio at this time is recorded as the second ratio and the raw material types at this time are recorded, wherein the first predetermined value is greater than the second predetermined value;
[0036] Mixing the determined first negative electrode active material, the first auxiliary material and the first solvent in a determined first ratio to obtain a first active layer slurry;
[0037] Mixing the determined second negative electrode active material, the second auxiliary material and the second solvent in a determined second ratio to obtain a second active layer slurry;
[0038] Applying the first active layer slurry on the surface of the negative electrode current collector to form a first active layer;
[0039] The second active layer slurry is coated on the surface of the first active layer to form a second active layer, thereby obtaining a double-layer coated negative electrode sheet.
[0040] In the present invention, "1T powder compaction density" refers to the powder compaction density under 1T pressure.
[0041] In the present invention, in the step of determining the first ratio, “raw material type” refers to the types of the first negative electrode active material and the first auxiliary material.
[0042] In the present invention, in the step of determining the second ratio, "raw material type" refers to the types of the second negative electrode active material and the second auxiliary material.
[0043] In the present invention, the mixing ratio refers to a mass mixing ratio.
[0044] In the present invention, in the step of determining the first ratio and the second ratio, a small amount of the first negative electrode active material and the first auxiliary material and a small amount of the second negative electrode active material and the second auxiliary material can be taken to adjust the mixing ratio to avoid wasting raw materials.
[0045] In the present invention, in the step of preparing the first active layer slurry, the types of the first negative electrode active material and the first auxiliary material used are the types of the first negative electrode active material and the first auxiliary material contained in the first mixture when the first ratio is recorded.
[0046] In the present invention, in the step of preparing the second active layer slurry, the types of the second negative electrode active material and the second auxiliary material used are the types of the second negative electrode active material and the second auxiliary material contained in the second mixture when recording the second ratio.
[0047] In some embodiments, the step of determining the first ratio includes: setting multiple gradient mixing ratios, mixing the first negative electrode active material and the first auxiliary material according to the multiple mixing ratios and then drying them to obtain multiple first mixtures, and determining the mixing ratio that can make the 1T powder compaction density of the first mixture reach a first predetermined value as the first ratio.
[0048] In some embodiments, the step of determining the second ratio includes: setting a plurality of gradient mixing ratios, mixing the second negative electrode active material and the second auxiliary material according to the plurality of mixing ratios respectively and then drying them to obtain a plurality of second mixtures, and determining the mixing ratio that can make the 1T powder compaction density of the second mixture reach a second predetermined value as the second ratio.
[0049] In some embodiments, the first active layer slurry may be coated on one surface of the negative electrode current collector. In other embodiments, the first active layer slurry may also be coated on both surfaces of the negative electrode current collector.
[0050] In some embodiments, the first predetermined value is 1.7 to 2.2 g / cm 3 , preferably 1.7 to 2.0 g / cm 3 The second predetermined value is 1.3 to 1.8 g / cm 3 , preferably 1.5 to 1.8 g / cm 3 .
[0051] Control the 1T powder compaction density of the first mixture to 1.7-2.2g / cm 3 At the same time, the 1T powder compaction density of the second mixture is controlled to reach 1.3-1.8g / cm 3 , which can ensure that the compaction density of the first active layer is greater than the compaction density of the second active layer, and the porosity of the first active layer is less than that of the second active layer, forming a gradient pore structure that reduces the diffusion impedance of lithium ions, improving the wetting and liquid retention effect, and can also be used for Li + Rapid migration provides more effective channels and reduces Li in the inner layer of the electrode dressing + Diffusion polarization improves the cycle life and charging rate of the battery.
[0052] In some specific embodiments, the first predetermined value may be, for example, 1.7 g / cm 3 , 1.8g / cm 3 , 1.9g / cm 3 , 2.0g / cm 3 , 2.1g / cm 3 or 2.2g / cm 3 .
[0053] In some specific embodiments, the second predetermined value may be, for example, 1.3 g / cm3 , 1.4g / cm 3 , 1.5g / cm 3 , 1.6g / cm 3 , 1.7g / cm 3 or 1.8 g / cm 3 .
[0054] In some embodiments, the first auxiliary material includes one or more of a first binder, a first conductive agent, and a first dispersant.
[0055] In some embodiments, the second auxiliary material includes one or more of a second binder, a second conductive agent, and a second dispersant.
[0056] The use of a binder in the slurry is beneficial to improving the adhesion of the coating on the negative electrode current collector and the adhesion between the coatings, and reducing the occurrence of coating shedding. The use of a conductive agent can reduce the internal resistance of the battery and improve the charge and discharge performance of the battery. The use of a dispersant is beneficial to uniformly disperse particles or powders in a liquid to form a stable suspension or emulsion, prevent precipitation and aggregation, and improve coating uniformity and pole piece performance. In the present invention, "coating" and "active layer" have the same meaning.
[0057] In some embodiments, the mass ratio of the first negative electrode active material, the first conductive agent, the first dispersant, and the first binder is (94-97.4): (0.8-1.4): (0.2-1.5): (1.4-3.6). Optimizing the amount relationship between the components is conducive to regulating the influence of the relative compressive strength of the first active layer formed by the auxiliary materials, so that the compaction density of the first active layer is maintained within a reasonable range, and the cycle performance and charging rate of the battery are improved.
[0058] In some specific embodiments, the mass ratio of the first negative electrode active material, the first conductive agent, the first dispersant, and the first binder may be, for example, 95.2: 1: 1.2: 2.6, 95.7: 0.8: 1.2: 2.3, 96.4: 0.8: 1.3: 1.5, 94: 1.4: 1: 3.6, or 97: 0: 1: 1: 1. Optionally, the mass ratio of the first negative electrode active material, the first conductive agent, the first dispersant, and the first binder is (95.2-96.4): (0.8-1): (1.2-1.3): (1.5-2.6).
[0059] In some embodiments, the mass ratio of the second negative electrode active material, the second conductive agent, the second dispersant, and the second binder is (96.4-99): (0-0.5): (0.5-1.5): (0.1-2.6). Optimizing the dosage relationship between the components is conducive to regulating the influence of the relative compressive strength of the second active layer formed by the auxiliary materials, so that the compaction density of the second active layer is maintained within a reasonable range, and the cycle performance and charging rate of the battery are improved.
[0060] In some specific embodiments, the mass ratio of the second negative electrode active material, the second conductive agent, the second dispersant, and the second binder may be, for example, 97.7:0.3:0.5:1.5, 97.2:0.3:0.5:2, 96.7:0.4:0.5:2.4, 96.4:0.5:1.5:1.6, or 99:0.2:0.5:0.3. Optionally, the mass ratio of the second negative electrode active material, the second conductive agent, the second dispersant, and the second binder is (96.7-97.7): (0.3-0.5): (0.5-1.5): (1.5-2.4).
[0061] In some specific embodiments, the first binder and the second binder each include one or more of styrene-butadiene rubber, polyacrylic acid, sodium polyacrylate, polyacrylamide, polyvinyl alcohol, sodium alginate, polymethacrylic acid and carboxymethyl chitosan.
[0062] In some specific embodiments, the first conductive agent and the second conductive agent each include one or more of superconducting carbon, acetylene black, carbon black, Ketjen black, carbon dots, carbon nanotubes, graphene, and carbon nanofibers.
[0063] In some specific embodiments, the first dispersant and the second dispersant each include one or more of sodium carboxymethyl cellulose 350 , sodium carboxymethyl cellulose 500 , sodium carboxymethyl cellulose 2300 , and sodium carboxymethyl cellulose 2500 .
[0064] In some embodiments, the proportion of the first conductive agent in the total mass of the first negative electrode active material and the first auxiliary material is greater than the proportion of the second conductive agent in the total mass of the second negative electrode active material and the second auxiliary material to ensure that the coating and the foil have good conductivity and adhesion.
[0065] In some embodiments, in order to reduce the compressive resistance of the first active layer, in the first active layer, the first binder includes polyacrylic acid and the first dispersant includes sodium carboxymethyl cellulose; wherein the proportion of polyacrylic acid in the total mass of the first negative electrode active material and the first auxiliary material is less than the proportion of sodium carboxymethyl cellulose in the total mass of the first negative electrode active material and the first auxiliary material.
[0066] In some embodiments, in order to improve the compressive resistance of the second active layer, in the second active layer, the second binder includes polyacrylic acid and the second dispersant includes sodium carboxymethyl cellulose; wherein the proportion of polyacrylic acid in the total mass of the second negative electrode active material and the second auxiliary material is greater than the proportion of sodium carboxymethyl cellulose in the total mass of the second negative electrode active material and the second auxiliary material.
[0067] In some embodiments, the first negative active material and the second negative active material each include graphite.
[0068] In some specific embodiments, the graphite includes one or more of natural graphite, modified natural graphite, and artificial graphite.
[0069] In some embodiments, the compaction density of the first active layer is greater than the compaction density of the second active layer, and the porosity of the first active layer is less than the porosity of the second active layer. The double-layer coated negative electrode sheet prepared by the method of the present invention can ensure that the compaction density of the first active layer is greater than the compaction density of the second active layer, and the porosity of the first active layer is less than the porosity of the second active layer, forming a gradient pore structure that reduces the diffusion impedance of lithium ions, improves the infiltration and liquid retention effect, and can also be Li + Rapid migration provides more effective channels and reduces Li in the inner layer of the electrode dressing + Diffusion polarization improves the cycle life and charging rate of the battery.
[0070] In some embodiments, the surface density ratio of the second active layer to the first active layer is 1:(0.1-9).
[0071] In some embodiments, the first active layer slurry is coated on both surfaces of the negative electrode current collector, and the first active layer is formed after rolling, and then the second active layer slurry is coated on the surface of the first active layer, and the second active layer is formed after rolling, so as to obtain a double-sided double-layer coated negative electrode sheet. After baking, the double-sided surface density of the negative electrode sheet is 200-350g / m 2 .
[0072] In some specific embodiments, the area density ratio of the second active layer to the first active layer may be 1:0.1, 1:0.5, 1:1, 1:2, 1:3, 1:4, 1:5, 1:6, 1:7, 1:8 or 1:9.
[0073] In some embodiments, the first solvent and the second solvent each include water.
[0074] In some embodiments, the solid content of the first active layer slurry is 50%-55%, and the solid content of the second active layer slurry is 53%-58%.
[0075] In some embodiments, the gram capacity of the first active layer is 352-380 mAh / g. The gram capacity of the second active layer is 340-370 mAh / g.
[0076] In some embodiments, the first negative electrode active material is graphite, and the D50 particle size of the graphite is 12 to 18 micrometers, and the D90 particle size of the graphite is 25 to 30 micrometers.
[0077] In some embodiments, the second negative electrode active material is graphite, and the D50 particle size of the graphite is 10 to 15 micrometers, and the D90 particle size of the graphite is 20 to 25 micrometers.
[0078] The scheme of the present invention will be explained below in conjunction with the embodiments. It will be appreciated by those skilled in the art that the following embodiments are only used to illustrate the present invention and should not be considered as limiting the scope of the present invention. Where specific techniques or conditions are not indicated in the embodiments, the techniques or conditions described in the literature in this area or the product specifications are used. The reagents or instruments used are not indicated by the manufacturer and are all conventional products that can be obtained commercially.
[0079] Example 1
[0080] (1) Selecting raw materials as graphite, conductive carbon black (SP), sodium carboxymethyl cellulose (CMC), polyacrylic acid (PAA) and styrene-butadiene rubber (SBR). With a gradient of 0.1% and a sum of CMC and PAA contents of 2%, multiple gradient mixing ratios are set. Specifically, with 95.2% graphite, 1.0% SP, 1.8% SBR and a sum of CMC and PAA contents of 2%, a gradient of CMC:PAA:SBR=2.0:0:1.8, 1.8:0.2:1.8, 1.6:0.4:1.8, 1.4:0.6:1.8, 1.2:0.8:1.8 and 1.0:1.0:1.8 is designed. Graphite, SP, CMC, PAA and SBR are mixed and dried according to multiple mixing ratios to obtain multiple first mixtures. The 1T powder compaction density of the first mixture is tested, and the 1T powder compaction density of the first mixture can reach a first predetermined value (i.e., 1.9 g / cm 3 ) is determined as the first ratio, and the first ratio (mass ratio of graphite, SP, CMC, PAA and SBR) is 95.2:1.0:1.2:0.8:1.8. The method for determining the first ratio in other embodiments and comparative examples is the same as step (1) of embodiment 1, by setting multiple gradient mixing ratios, and selecting the mixing ratio that can meet the first predetermined value as the first ratio.
[0081] (2) Selecting raw materials as graphite, conductive carbon black (SP), sodium carboxymethyl cellulose (CMC), polyacrylic acid (PAA) and styrene-butadiene rubber (SBR). With a gradient of 0.1% and a sum of CMC and PAA content of 1.5%, multiple gradient mixing ratios are set. Specifically, with a graphite content of 97.7%, SP of 0.3%, SBR content of 0.5%, and a sum of CMC and PAA content of 1.5%, a gradient of CMC:PAA:SBR=0.1:1.4:1.8, 0.3:1.2:1.8, 0.5:1.0:1.8, and 0.7:0.8:1.8 is designed. Graphite, SP, CMC, PAA and SBR are mixed and dried according to multiple mixing ratios to obtain multiple second mixtures. The 1T powder compaction density of the second mixture is tested. The 1T powder compaction density of the second mixture can reach the second predetermined value (i.e., 1.5 g / cm 3 ) is determined as the second ratio, and the second ratio (mass ratio of graphite, SP, CMC, PAA and SBR) is 97.7:0.3:0.5:1.0:0.5. The method for determining the second ratio in other embodiments and comparative examples is the same as step (2) of embodiment 1, by setting multiple gradient mixing ratios, and selecting the mixing ratio that can meet the second predetermined value as the second ratio.
[0082] (3) Graphite, SP, and CMC are mixed uniformly in proportion; then PAA, SBR, and water are added thereto in proportion, and the mass ratio of graphite, SP, CMC, PAA, and SBR is 95.2:1.0:1.2:0.8:1.8, and the mixture is mixed thoroughly to obtain a first active layer slurry, wherein the solid content of the slurry is 55%, wherein the 1T powder compaction density of all solid substances in the first active layer slurry (i.e., the first mixture in step 1) is 1.9 g / cm 3 The compacted density of 1T graphite powder is 1.7g / cm 3 .
[0083] (4) Graphite, SP, and CMC are mixed uniformly in proportion; then PAA, SBR, and water are added thereto in proportion, and the mass ratio of graphite, SP, CMC, PAA, and SBR is 97.7:0.3:0.5:1.0:0.5, and the mixture is mixed thoroughly to obtain a second active layer slurry, wherein the solid content of the slurry is 52%, wherein the 1T powder compaction density of all solid substances in the second active layer slurry (i.e., the second mixture in step 2) is 1.5 g / cm 3 The compacted density of the graphite 1T powder is 1.4 g / cm 3 .
[0084] (5) coating the first active layer slurry and the second active layer slurry on one side of the negative electrode current collector 100 through a double-layer coating die head of a coating machine to form a first active layer 200 and a second active layer 300 on the surface of one side of the negative electrode current collector; after baking, coating the first active layer slurry and the second active layer slurry on the other side of the negative electrode current collector 100 to form a first active layer 200 and a second active layer 300 on the surface of the other side of the negative electrode current collector; after baking, rolling is performed to obtain the negative electrode sheet of the lithium ion battery (the surface density ratio of the second active layer to the first active layer is 1:1), as shown in FIG. Figure 1 shown.
[0085] (6) Preparation of positive electrode sheet
[0086] Preparation method of positive electrode sheet: take polyvinylidene fluoride (PVDF) binder and dissolve it in N-methylpyrrolidone (NMP) solvent, stir it thoroughly to dissolve and form a clear solution; add conductive agent conductive carbon black (SP) and lithium iron phosphate (LFP) active material to the above clear solution, wherein the mass ratio of LFP, SP and PVDF is 8:1:1, stir evenly to obtain a slurry with certain fluidity, and the above slurry is coated on both sides of a 13μm thick metal aluminum foil, dried to obtain a positive electrode sheet, and then cold pressed and slit), and then the positive electrode tab made of 0.1mm thick tab aluminum strip is welded to the aluminum foil to obtain a positive electrode sheet.
[0087] (7) Preparation of lithium-ion batteries
[0088] The prepared negative electrode sheet, positive electrode sheet and isolation membrane are stacked to form a battery cell, and then the battery cell is installed in the battery aluminum-plastic film, and the electrolyte is injected into it. The soft-pack battery is then produced through processes such as formation and capacity division.
[0089] Example 2
[0090] A negative electrode sheet and a lithium-ion battery were prepared according to the method of Example 1, except that:
[0091] In step 1, the first predetermined value is 1.8 g / cm 3 , the first ratio (mass ratio) is 95.7:0.8:1.2:0.5:1.8;
[0092] In step 2, the second predetermined value is 1.6 g / cm 3 , the second ratio (mass ratio) is 97.2:0.3:0.5:1.5:0.5;
[0093] In step 3, the mass ratio of graphite, SP, CMC, PAA and SBR is 95.7:0.8:1.2:0.5:1.8, and the 1T powder compaction density of all solid substances in the first active layer slurry (i.e., the first mixture in step 1) is 1.8 g / cm 3The compacted density of 1T graphite powder is 1.6g / cm 3 ;
[0094] In step 4, the mass ratio of graphite, SP, CMC, PAA and SBR is 97.2:0.3:0.5:1.5:0.5, the solid content of the slurry is 51%, and the 1T powder compaction density of all solid substances in the second active layer slurry (i.e., the second mixture of step 2) is 1.6 g / cm 3 The compacted density of the graphite 1T powder is 1.5 g / cm 3 .
[0095] Example 3
[0096] A negative electrode sheet and a lithium-ion battery were prepared according to the method of Example 1, except that:
[0097] In step 1, the first predetermined value is 1.7 g / cm 3 , the first ratio (mass ratio) is 96.4:0.8:1.3:0:1.5;
[0098] In step 2, the second predetermined value is 1.6 g / cm 3 , the second ratio (mass ratio) is 96.7:0.4:0.5:1.8:0.6;
[0099] In step 3, the mass ratio of graphite, SP, CMC, PAA and SBR is 96.4:0.8:1.3:0:1.5, the solid content of the slurry is 56%, and the 1T powder compaction density of all solid substances in the first active layer slurry (i.e., the first mixture in step 1) is 1.7 g / cm 3 The compacted density of 1T graphite powder is 1.4g / cm 3 ;
[0100] In step 4, the mass ratio of graphite, SP, CMC, PAA and SBR is 96.7:0.4:0.5:1.8:0.6, the solid content of the slurry is 53%, and the 1T powder compaction density of all solid substances in the second active layer slurry (i.e., the second mixture of step 2) is 1.6 g / cm 3 The compacted density of the graphite 1T powder is 1.6 g / cm 3 .
[0101] Example 4
[0102] A negative electrode sheet and a lithium-ion battery were prepared according to the method of Example 3, with the differences shown in Tables 1 and 3 below.
[0103] Example 5
[0104] A negative electrode sheet and a lithium-ion battery were prepared according to the method of Example 1, with the differences shown in Tables 1 and 3 below.
[0105] Comparative Example 1
[0106] A negative electrode sheet and a lithium-ion battery were prepared according to the method of Example 1, except that:
[0107] In step 1, the first predetermined value is 1.5 g / cm 3 , the first ratio (mass ratio) is 97.7:0.3:0.5:1.0:0.5;
[0108] In step 2, the second predetermined value is 2.9 g / cm 3 , the second ratio (mass ratio) is 95.2:1.0:1.2:0.8:1.8;
[0109] In step 3, the mass ratio of graphite, SP, CMC, PAA and SBR is 97.7:0.3:0.5:1.0:0.5, the solid content of the slurry is 52%, and the 1T powder compaction density of all solid substances in the first active layer slurry (i.e., the first mixture in step 1) is 1.5 g / cm 3 The compacted density of 1T graphite powder is 1.4g / cm 3 ;
[0110] In step 4, the mass ratio of graphite, SP, CMC, PAA and SBR is 95.2:1.0:1.2:0.8:1.8, the solid content of the slurry is 55%, and the 1T powder compaction density of all solid substances in the second active layer slurry (i.e., the second mixture of step 2) is 1.9 g / cm 3 The compacted density of the graphite 1T powder is 1.7 g / cm 3 .
[0111] Comparative Example 2
[0112] A negative electrode sheet and a lithium-ion battery were prepared according to the method of Example 2, except that:
[0113] In step 1, the first predetermined value is 1.6 g / cm 3 , the first ratio (mass ratio) is 97.2:0.3:0.5:1.5:0.5;
[0114] In step 2, the second predetermined value is 1.7 g / cm 3 , the second ratio (mass ratio) is 95.7:0.8:1.2:0.5:1.8;
[0115] In step 3, the mass ratio of graphite, SP, CMC, PAA and SBR is 97.2:0.3:0.5:1.5:0.5, the solid content of the slurry is 51%, and the 1T powder compaction density of all solid substances in the first active layer slurry (i.e., the first mixture of step 1) is 1.6 g / cm3 The compacted density of 1T graphite powder is 1.5g / cm 3 ;
[0116] In step 4, the mass ratio of graphite, SP, CMC, PAA and SBR is 95.7:0.8:1.2:0.5:1.8, the solid content of the slurry is 55%, and the 1T powder compaction density of all solid substances in the second active layer slurry (i.e., the second mixture of step 2) is 1.8 g / cm 3 The compacted density of the graphite 1T powder is 1.6 g / cm 3 .
[0117] Comparative Example 3
[0118] A negative electrode sheet and a lithium-ion battery were prepared according to the method of Example 3, except that:
[0119] In step 1, the first predetermined value is 1.6 g / cm 3 , the first ratio (mass ratio) is 96.7:0.4:0.5:1.8:0.6;
[0120] In step 2, the second predetermined value is 1.7 g / cm 3 , the second ratio (mass ratio) is 96.4:0.8:1.3:0:1.5;
[0121] In step 3, the mass ratio of graphite, SP, CMC, PAA and SBR is 96.7:0.4:0.5:1.8:0.6, the solid content of the slurry is 53%, and the 1T powder compaction density of all solid substances in the first active layer slurry (i.e., the first mixture in step 1) is 1.6 g / cm 3 The compacted density of 1T graphite powder is 1.6g / cm 3 ;
[0122] In step 4, the mass ratio of graphite, SP, CMC, PAA and SBR is 96.4:0.8:1.3:0:1.5, the solid content of the slurry is 56%, and the 1T powder compaction density of all solid substances in the second active layer slurry (i.e., the second mixture of step 2) is 1.7 g / cm 3 The compacted density of the graphite 1T powder is 1.4 g / cm 3 .
[0123] Table 1
[0124]
[0125] The fast charge rate and cycle performance of the lithium ion batteries prepared in Examples 1-5 and Comparative Examples 1-3 were tested.
[0126] 1.Charging rate test
[0127] The battery cell was constant capacity obtained to obtain the capacity Q0, constant capacity conditions: the battery cell was allowed to stand at 25°C for 30 min, discharged at 0.33C to 2.0V, charged at 0.33C constant current to 3.65V, charged at constant voltage with a cutoff current of 0.05C, and discharged at 0.33C to 2.0V to obtain the capacity Q0.
[0128] With Q0 as 100% SOC, within the range of 0 to 80% SOC, at every 5% SOC, let I5 be the charging current from 0 to 5% SOC, I 10 is the charging current of 5~10% SOC, and so on; let C5 be the charging rate of 0~5% SOC, C5=I5 / Q0; C 10 The charge rate is 5~10% SOC, C 10 =I 10 / Q0, and so on. Adjust C5~C 80 The value is used to minimize the charging time of the battery cell without lithium deposition at 0-80% SOC, denoted by C. QC =2880 / (180 / C5+180 / C 10 +…+180 / C 80 ) is 0~80% SOC equivalent ratio.
[0129] The test results of Examples 1-5 and Comparative Examples 1-3 are shown in Table 3.
[0130] 2. Cycle performance test
[0131] The battery cell was fixed to obtain the capacity Q0. The fixed capacity conditions were as follows: the battery cell was allowed to stand at 25°C for 30 min, discharged at 0.33C to 2.0V, charged at 0.33C constant current to 3.65V, charged at constant voltage with a cutoff current of 0.05C, and discharged at 0.33C to 2.0V to obtain the capacity Q0.
[0132] The battery cell was left to stand at 25℃ for 30min and the charge rate was tested according to the C x According to the definition of Table 2 below, charge the battery to 80% SOC.
[0133] Table 2
[0134] step C Value Time / s <![CDATA[C5]]> 5.5 33 <![CDATA[C 10 ]]> 5.5 33 <![CDATA[C 15 ]]> 5.5 33 <![CDATA[C 20 ]]> 5.5 33 <![CDATA[C 25 ]]> 5.5 33 <![CDATA[C 30 ]]> 5.5 33 <![CDATA[C 35 ]]> 5.5 33 <![CDATA[C 40 ]]> 5.5 33 <![CDATA[C 45 ]]> 5 36 <![CDATA[C 50 ]]> 5 36 <![CDATA[C 55 ]]> 4.8 38 <![CDATA[C 60 ]]> 4.2 43 <![CDATA[C 65 ]]> 3.6 50 <![CDATA[C 70 ]]> 3 60 <![CDATA[C 75 ]]> 2.5 72 <![CDATA[C 80 ]]> 2 90
[0135] The battery cell was charged to full capacity, charged to 3.65V at 0.33C constant current, charged at constant voltage, discharged to 2.0V at 1C, and the process was repeated. The test was terminated when the capacity decayed to 80% Q0. The test results are shown in Table 3. The cycle test results of Examples 1-3 and Comparative Examples 1-3 are shown in Table 3. Figure 2 shown.
[0136] Table 3 Charging rate test results of the embodiments and comparative examples
[0137]
[0138]
[0139] By comparing Examples 1-5 with Comparative Example 1, it can be seen that the present invention first adjusts the mixing ratio of the first negative electrode active material and the first auxiliary material and the mixing ratio of the second negative electrode active material and the second auxiliary material before preparing the active layer slurry, so that the 1T powder compaction density of the first mixture and the second mixture is within a predetermined range, and then the active layer slurry is prepared, coated, and rolled after determining the type and mixing ratio of the raw materials, so that the compaction density difference between the formed first active layer and the second active layer can be ensured to reach the ideal target difference. Applying the negative electrode sheet of the present invention to the battery can improve the cycle life and charging rate of the battery.
[0140] By comparing Example 3 with Comparative Example 3, it can be seen that even if the compaction density of the first active layer graphite 1T powder is greater than the compaction density of the second active layer graphite 1T powder, when the compaction density of the 1T powder of the first mixture is less than the compaction density of the 1T powder of the second mixture, it is impossible to achieve that the compaction density of the first active layer is greater than the compaction density of the second active layer. This also shows that the present application solves the problem in the related art that the target difference cannot be achieved by only controlling the compaction density of the graphite powder.
[0141] By comparing Example 1 with Example 4, it can be seen that when the proportion of polyacrylic acid in the total mass of the first negative electrode active material and the first auxiliary material is less than the proportion of sodium carboxymethyl cellulose in the total mass of the first negative electrode active material and the first auxiliary material, it is beneficial to improve the cycle life and charge rate of the battery.
[0142] By comparing Example 1 with Example 5, it can be seen that when the proportion of polyacrylic acid in the total mass of the second negative electrode active material and the second auxiliary material is greater than the proportion of sodium carboxymethyl cellulose in the total mass of the second negative electrode active material and the second auxiliary material, it is beneficial to improve the cycle life and charge rate of the battery.
[0143] In the description of this specification, the description with reference to the terms "one embodiment", "some embodiments", "example", "specific example", or "some examples" etc. means that the specific features, structures, materials or characteristics described in conjunction with the embodiment or example are included in at least one embodiment or example of the present invention. In this specification, the schematic representations of the above terms do not necessarily refer to the same embodiment or example. Moreover, the specific features, structures, materials or characteristics described may be combined in any one or more embodiments or examples in a suitable manner. In addition, those skilled in the art may combine and combine the different embodiments or examples described in this specification and the features of the different embodiments or examples, unless they are contradictory.
[0144] Although the embodiments of the present invention have been shown and described above, it is to be understood that the above embodiments are exemplary and are not to be construed as limitations of the present invention. A person skilled in the art may change, modify, replace and vary the above embodiments within the scope of the present invention.
Claims
1. A method for preparing a double-layer coated negative electrode sheet, characterized in that: The following steps are involved: The first negative electrode active material and the first auxiliary material are mixed and dried to obtain a first mixture, and the 1T powder compaction density of the first mixture reaches a first predetermined value by adjusting the raw material types and / or the mixing ratio, and the mixing ratio at this time is recorded as the first ratio and the raw material types at this time are recorded; The second negative electrode active material and the second auxiliary material are mixed and dried to obtain a second mixture, and the 1T powder compaction density of the second mixture reaches a second predetermined value by adjusting the raw material types and / or the mixing ratio, and the mixing ratio at this time is recorded as the second ratio and the raw material types at this time are recorded, wherein the first predetermined value is greater than the second predetermined value; Mixing the determined first negative electrode active material, the first auxiliary material and the first solvent in a determined first ratio to obtain a first active layer slurry; Mixing the determined second negative electrode active material, the second auxiliary material and the second solvent in a determined second ratio to obtain a second active layer slurry; Applying the first active layer slurry on the surface of the negative electrode current collector to form a first active layer; The second active layer slurry is coated on the surface of the first active layer to form a second active layer, thereby obtaining a double-layer coated negative electrode sheet.
2. The method according to claim 1, characterized in that The first predetermined value is 1.7 to 2.2 g / cm 3 , preferably 1.7 to 2.0 g / cm 3 The second predetermined value is 1.3 to 1.8 g / cm 3 , preferably 1.5 to 1.8 g / cm 3 .
3. The method according to claim 1, characterized in that The first auxiliary material includes one or more of a first binder, a first conductive agent and a first dispersant; Optionally, the second auxiliary material includes one or more of a second binder, a second conductive agent and a second dispersant.
4. The method according to claim 3, characterized in that: The mass ratio of the first negative electrode active material, the first conductive agent, the first dispersant, and the first binder is (94-97.4): (0.8-1.4): (0.2-1.5): (1.4-3.6).
5. The method according to claim 3, characterized in that: The mass ratio of the second negative electrode active material, the second conductive agent, the second dispersant, and the second binder is (96.4-99): (0-0.5): (0.5-1.5): (0.1-2.6).
6. The method according to claim 3, characterized in that The proportion of the first conductive agent in the total mass of the first negative electrode active material and the first auxiliary material is greater than the proportion of the second conductive agent in the total mass of the second negative electrode active material and the second auxiliary material.
7. The method according to claim 3, characterized in that The first binder and the second binder each include one or more of styrene-butadiene rubber, polyacrylic acid, sodium polyacrylate, polyacrylamide, polyvinyl alcohol, sodium alginate, polymethacrylic acid and carboxymethyl chitosan; Optionally, the first conductive agent and the second conductive agent each include one or more of superconducting carbon, acetylene black, carbon black, Ketjen black, carbon dots, carbon nanotubes, graphene and carbon nanofibers; Optionally, the first dispersant and the second dispersant each include one or more of sodium carboxymethyl cellulose 350 , sodium carboxymethyl cellulose 500 , sodium carboxymethyl cellulose 2300 , and sodium carboxymethyl cellulose 2500 .
8. The method according to claim 7, characterized in that In the first active layer, the first binder includes polyacrylic acid, and the first dispersant includes sodium carboxymethyl cellulose; wherein the proportion of polyacrylic acid in the total mass of the first negative electrode active material and the first auxiliary material is less than the proportion of sodium carboxymethyl cellulose in the total mass of the first negative electrode active material and the first auxiliary material; Optionally, in the second active layer, the second binder includes polyacrylic acid and the second dispersant includes sodium carboxymethyl cellulose; wherein the proportion of polyacrylic acid in the total mass of the second negative electrode active material and the second auxiliary material is greater than the proportion of sodium carboxymethyl cellulose in the total mass of the second negative electrode active material and the second auxiliary material.
9. The method according to claim 1, characterized in that: The first negative electrode active material and the second negative electrode active material each include graphite; Optionally, the graphite includes one or more of natural graphite, modified natural graphite, and artificial graphite.
10. The method according to claim 1, characterized in that The compaction density of the first active layer is greater than the compaction density of the second active layer, and the porosity of the first active layer is less than the porosity of the second active layer; Optionally, the surface density ratio of the second active layer to the first active layer is 1:(0.1-9).
Citation Information
Cited By
Double-layer coated negative pole piece, preparation method thereof and lithium ion battery
CN120784272A